Motivations on the choice of post-consumer clothing disposal routes by Brazilian consumers - Julia Helena Galante Amaral; Eduardo Eugênio Spers (Academia Environmental Sciences and Sustainability)
Fast fashion has boosted apparel production, encouraging consumers to buy and discard at an accelerated pace because garments are viewed as easily replaceable items. This paper investigates motivating factors influencing Brazilian consumers’ choices in post-consumer clothing disposal. The choice of clothing disposal routes depends both on the consumer’s motivations and the garment’s attributes. The empirical investigation was developed using a quantitative approach of multivariate analysis, involving 652 survey participants, to test nine hypotheses using structural equation modeling. Variables explored include consumer’s motivating factors (personal motivating operation, product attributes, and socio-environmental awareness) and disposal route choices (reuse, resale or donation, or discard as waste). Our results validate four hypotheses, indicating that stronger personal motivation reduces garment intention to reuse but increases the likelihood of reselling or donating, and socio-environmental awareness discourages clothing disposal as waste. Common post-consumer clothing disposal methods include donating to relatives or friends, while using retail stores’ garment collection services is less prevalent. This paper contributes to the literature about post-consumer behaviors regarding clothing in the Brazilian context. Also, it elucidates opportunities for consumers, governments, and fashion market players with the end-of-life of garments, by valuing textile waste and promoting a sustainable transition toward circular fashion.